السلوك الإنساني في ظل الجوائح :جائحة فيروس كورونا المستجد بالجزائر نموذجا - خيرار, نبيلة (University of Eloued جامعة الوادي, 2020)
تعتبر جائحة فيروس كورونا المستجد التي ألمت بالعالم في الظرفية الحالية ودفعت بلدانه نحو التدبير الاستعجالي لاحتوائها واحدة من الموضوعات الرئيسية التي تستحق البحث والدراسة سوسيولوجيا، لفهم تأثيراتها على كل جوانب الحياة اليومية للأفراد، خاصة فيما يتعلق بأنماط السلوك وما تحتويه من أنساق للفعل والتفكير والانطباع والتمثل تجاه الجائحة. وبالاعتماد على ماهو متوفر من بيانات مستقاة من مواقع التواصل الاجتماعي وما تبثه وسائل الإعلام وما نعايشه من تمظهرات للسلوك الإنساني كردة فعل تجاه الجائحة والإجراءات الاحترازية المتخذة للوقاية منها والحد من انتشارها ، نساهم بالمقالي الحالي كمحاولة لقراءة وتفسير أهم السلوكات المصاحبة للجائحة بالمجتمع الجزائري ونعني بها: 1- التغير في أنماط التفاعل الاجتماعي من الواقعي إلى الافتراضي. 2- تنامي سلوكات الوصم الاجتماعي واللهفة في الشراء. 3- العودة إلى السلوك التقليدي في العلاج. 4- إحياء وتعزيز سلوك التضامن الاجتماعي. 5- التحول في طرق التحية. 6- تصاعد هاجس المؤامرة والتفسيرات الغيبية للوباء. وخلصنا إلى اعتبار هذه السلوكات منتجا لحالة عدم اليقين والهلع الجماعي وترتبط ارتباطا وثيقا ببنية المجتمع الجزائري وما تتضمنه من أنماط معيشية ومرجعيات ثقافية ودينية ومستويات الوعي الصحي والاجتماعي للسكان. الكلمات المفتاحية: السلوك- المجتمع الجزائري- جائحة فيروس كورونا- الهلع الجماعي- كوفيد19- الإجراءات الاحترازية Abstract: The emerging Coronavirus pandemic that struck the world in the current circumstance, and pushed its countries towards emergency management to contain it , is one of the main topics that deserve sociological research and study to understand its effects on all aspects of the individuals’ daily life, especially with regard to behavior patterns which contain types of action, thinking, impression and assimilation towards the pandemic . Based on what is available from the data obtained from social networks and the media, and what we experience in terms of human behavior in response towards the pandemic and the prevention procedure from it and prevent its spread, we contribute by the current article as an attempt to read and explain the most important behaviors associated with the pandemic in the Algerian society, we mean: 1-Change in the patterns of social interaction from real to virtual. 2-Growing social stigmatizing and eagerness to buy . 3-Return to traditional treatment behavior. 4-Promote and revive social solidarity behavior . 5-Shift in greeting salutations . 6- Increasing of conspiracy obsession and metaphysical interpretations for the epidemic. We concluded that these behaviors are considered as a product of a state of uncertainty and collective panic, and are closely related to the structure of Algerian society, including the lifestyles, cultural and religious references, and the population's levels of health and social awareness . keywords: Behavior ; Algerian society ; Coronavirus pandemic ; Collective panic ;Covid-19; Prevention procedure
مقال
Keywords: السلوك ; المجتمع الجزائري ; جائحة فيروس كورونا ; الهلع الجماعي ; كوفيد19 ; الإجراءات الاحترازية